2005
DOI: 10.1128/aem.71.9.5532-5543.2005
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Uranium by Cells and S-Layer Sheets of Bacillus sphaericus JG-A12

Abstract: Bacillus sphaericus JG-A12 is a natural isolate recovered from a uranium mining waste pile near the town of Johanngeorgenstadt in Saxony, Germany. The cells of this strain are enveloped by a highly ordered crystalline proteinaceous surface layer (S-layer) possessing an ability to bind uranium and other heavy metals. Purified and recrystallized S-layer proteins were shown to be phosphorylated by phosphoprotein-specific staining, inductive coupled plasma mass spectrometry analysis, and a colorimetric method. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
182
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 243 publications
(205 citation statements)
references
References 48 publications
(54 reference statements)
19
182
0
4
Order By: Relevance
“…This is in agreement with the results reported in the literatures of [23][24][25]. And this may suggest that Pb (II) and Cd (II) immobilized on surface of D. radiodurans [26].…”
Section: Xrdsupporting
confidence: 83%
“…This is in agreement with the results reported in the literatures of [23][24][25]. And this may suggest that Pb (II) and Cd (II) immobilized on surface of D. radiodurans [26].…”
Section: Xrdsupporting
confidence: 83%
“…Microorganisms can potentially affect radionuclide migration by various processes including biosorption, biomineralization, intracellular accumulation, biotransformations, etc. [11][12][13][14][15][16][17]. In addition, microbial occurrence can influence the release of radionuclides by changing geochemical conditions (especially pH and Eh), by producing organic complexes [18].…”
Section: Introductionmentioning
confidence: 99%
“…12,13) Although S-layers have been identified in some B. sphaericus and their structures and re-assembly characteristics have been described, 3,6,14) the occurrence of S-layers is not well documented in insect pathogenic B. sphaericus strains, and there is no report on the relationship between S-layer of pathogenic B. sphaericus and its toxicity against mosquito larvae.…”
mentioning
confidence: 99%
“…3,4) S-layers play key roles in the interaction between bacterial cells and environment as protective coats, structures involved in cell adhesion and surface recognition, molecular sieves, attachment structures for high-molecular-mass extracellular proteins such as amylases, and in the sorption of toxic heavy metal ions. [5][6][7] Furthermore, it has been indicated that the S-layer might act as a virulence factor in several pathogenic bacteria, such as the S-layer protein produced by Bacillus thuringiensis GP1, which shows insecticidal activity against the coleopteran Epilachna varivestis, 8) and the S-layer of Lactobacillus acidophilus which mediates the adherence of the strains to avian intestinal epithelial cells. 9) B. sphaericus is a naturally occurring gram-positive soil bacterium that represents a strictly aerobic group of mesophilic endospore-forming bacteria.…”
mentioning
confidence: 99%